Liquidity Ratio and Solvency Ratio Analysis to Assess the Company's Financial Performance at PT. Wahana Pronactural Tbk for the Period 2019 – 2023 - Ningsih, Suci Cahya Widya; Pane, Sri Gustina; Rangkuti, Lusi Elviani (EDUCTUM: Journal Research, 2025)
This study aims to analyze liquidity and solvency ratios as tools for assessing the financial performance of PT Wahana Pronatural Tbk during the 2019–2023 period. The method used is descriptive quantitative, utilizing secondary data from the financial statements of companies listed on the Indonesia Stock Exchange. The ratios analyzed include the current ratio, quick ratio, and cash ratio to measure liquidity, as well as the debt-to-asset ratio (DAR) and debt-to-equity ratio (DER) to assess solvency. The analysis results show that the average current ratio of 212% reflects good liquidity. However, the quick ratio of 147% and the cash ratio of 20% indicate suboptimal conditions because they are below industry standards, caused by a decrease in cash and receivables and an increase in current liabilities from year to year. Meanwhile, the solvency aspect shows a significant increase in the company's debt since 2021, with a DAR of 29% and a DER of 43%. Despite the increase in financial risk, the company is still considered capable of meeting its short-term and long-term obligations. These findings are expected to provide evaluation material for management in efforts to improve the company's efficiency and financial stability.